Studying the removal of Hg(ІІ) from aqueous solution by using polyaniline and its nanocomposites. Issue 2 (26th January 2021) - Khalili, Reza; Karimi, Zeynab; Zazouli, Mohammad Ali
ABSTRACT: Polyaniline/antimony oxide (PAn/Sb2 O3 ) nanocomposite was prepared in aqueous media by the chemical polymerisation of aniline using ammonium peroxydisulfate (APS) as an oxidant in the presence of sodium dodecylbenzenesulfonate (DBSNa) and poly(vinyl pyrrolidone) (PVP) as surfactants. The application of PAn nanocomposite for the removal of Hg(II) from aqueous solutions was investigated. The chemical structure and morphology were studied by fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM) and X-ray diffraction (XRD). The results indicate that the Sb2 O3 and type of surfactant influence the properties of products. Adsorption studies were directed in a batch system as a function of solution pH, contact time and initial Hg(II) concentration. The optimum conditions of sorption were found to be: pH 6 and contact time of 40 min. The equilibrium adsorption capacity was obtained by using Langmuir and Freundlich isotherm models. The data were better fitted by using the Freundlich model. The results indicate that polyaniline/antimony oxide nanocomposite can be used as an effective adsorbent for the removal of Hg(II) from aqueous solution.